2006
DOI: 10.1159/000090071
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor Gene Therapy Slows Down the Progression of Diabetic Nephropathy in <i>db/db</i> Mice

Abstract: Background: Effect of hepatocyte growth factor (HGF) has scarcely been determined on diabetic nephropathy. Methods: Adenovirus encoding human HGF gene or LacZ gene (as the control) was injected into the hindlimb muscles of the C57BL/KsJ-db/db (db/db) mice at the age of 12 weeks, a model of genetic diabetes. Diabetic nephropathy was then evaluated at the age of 24 weeks. Results: The urine volume and albumin excretion progressively decreased in the control, whereas they remained unchanged in the HGF-treated gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 63 publications
3
18
0
Order By: Relevance
“…In addition, HO-1 is upregulated in MSCtreated animals. HO-1 is an enzyme that converts heme into carbon monoxide, iron, and biliverdin (which is later converted into bilirubin) [58,59]. It is known that HO-1 has an important protective role in many aspects of normal physiology and pathological states [58,60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, HO-1 is upregulated in MSCtreated animals. HO-1 is an enzyme that converts heme into carbon monoxide, iron, and biliverdin (which is later converted into bilirubin) [58,59]. It is known that HO-1 has an important protective role in many aspects of normal physiology and pathological states [58,60].…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 is an enzyme that converts heme into carbon monoxide, iron, and biliverdin (which is later converted into bilirubin) [58,59]. It is known that HO-1 has an important protective role in many aspects of normal physiology and pathological states [58,60]. Moreover, HO-1 deficiency is associated with increased fibrosis, tubular TGFb1 expression, inflammation, and enhanced EMT in obstructive kidney disease [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…To allow the persistent expression of HGF, the gene was transferred into muscle tissue using either electroporation (47,48), or ultrasound delivery (8), or adenoviral vectors (49). Other therapeutic approaches entailed the administration of recombinant HGF i.p.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, hepatocyte growth factor (HGF), originally identified and cloned as a mitogen for mature hepatocytes, exhibits potent renotropic properties and renoprotective role though the c-met receptor tyrosine kinase. A number of in vivo studies have demonstrated that HGF has potential therapeutic effect on diabetic nephropathy by suppressing ECM overproduction, but the relevant mechanism is little known [4,5,6,7]. Recent studies showed that HGF could retard oxidative stress-induced apoptosis as an antioxidant factor in many kinds of cells such as primary hepatocytes, human retinal-pigmented epithelial cells and human small airway epithelial cells[8,9,10].…”
Section: Introductionmentioning
confidence: 99%